Formative Research for Enhancing Instructional and Design Methods: A Focus on Virtual Reality (VR)-Based Learning Environment. - Chen, Chwen Jen (Springer Netherlands, 2009)
This paper reports the process of enhancing the instructional and design methods prescribed in an instructional design model for virtual reality (VR)-based learning environment. The study uses formative research to formatively evaluate the methods with the aim to generate hypotheses on how to improve the robustness of the model. The analysis of the data collected has revealed four principles that are hypothesized to be able to improve the model.